2016
DOI: 10.1186/s12961-016-0098-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysing key influences over actors’ use of evidence in developing policies and strategies in Nigeria: a retrospective study of the Integrated Maternal Newborn and Child Health strategy

Abstract: BackgroundEvidence-informed policymaking has been promoted as a means of ensuring better outcomes. However, what counts as evidence in policymaking lies within a spectrum of expert knowledge and scientifically generated information. Since not all forms of evidence share an equal validity or weighting for policymakers, it is important to understand the key factors that influence their preferences for different types of evidence in policy and strategy development.MethodA retrospective study was carried out at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The results can provide a basis for rational allocation of health resources and improvement of health policy planning. In the past, the government often introduced expert assessment as an essential means of policy assessment, but it is prone to subjective bias [ 23 ]. China's HPPs still lacks a comprehensive, easy-to-operate, scientific evaluation method of the pros and cons of such policies.…”
Section: Introductionmentioning
confidence: 99%
“…The results can provide a basis for rational allocation of health resources and improvement of health policy planning. In the past, the government often introduced expert assessment as an essential means of policy assessment, but it is prone to subjective bias [ 23 ]. China's HPPs still lacks a comprehensive, easy-to-operate, scientific evaluation method of the pros and cons of such policies.…”
Section: Introductionmentioning
confidence: 99%
“…There exists limited evidence on how policymakers take account of contextual issues. At a national level, a stable political system has a positive impact on policy development (Basaza, O'Connell, & Chapcakova, ; Mbachu et al, ) where the converse was found to hinder policy development (El‐Jardali, Bou‐Karroum, Ataya, El‐Ghali, & Hammoud, ). Health policymaking must sit comfortably within the wider national health strategic framework which can either act as a roadmap for policymaking or constrain attempts at policy reform (Mc Hugh, Perry, Bradley, & Brugha, ; Onwujekwe et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…First, our findings call for greater attention to be given to informal evidence, evidence based on personal experience, e.g. expert opinion and stakeholder consultations ( Mbachu et al. , 2016 ).…”
Section: Discussionmentioning
confidence: 99%